2016
DOI: 10.3329/jdmc.v24i1.29564
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Abo and Rhesus Blood Groups Among Blood Donor Attending Transfusion Medicine Department of Dhaka Medical College Hospital in 2014

Abstract: Objective: This study was aimed to identify the distribution patterns of ABO and Rh-D

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
6
1
Order By: Relevance
“…Several studies in Pakistan [ 7 , 25 ], Bangladesh [ 26 ], North India [ 26 ] have shown that blood group B was the predominant type followed by O, A and AB was the least.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in Pakistan [ 7 , 25 ], Bangladesh [ 26 ], North India [ 26 ] have shown that blood group B was the predominant type followed by O, A and AB was the least.…”
Section: Discussionmentioning
confidence: 99%
“…There was no big difference in the distribution of O and A blood groups (37.44% and 36.82%, respectively) in this study when compared with other studies in Saudi Arabia (47.45% and 26.2%) [ 19 ] and Nigeria (55.3% and 25.3%) [ 22 ] which showed significant differences in the frequency rates of O and A blood groups. Conversely, a study done by Sana and Tauseef reported that group A (28.947%) was the most prevalent followed by O (22.267%) [ 23 ], whereas other studies reported that B blood group (34.3% and 35.7%) was the most prevalent, followed by O (31.3% and 29.8%) [ 3 , 24 ]. The frequency rates of B and AB blood groups in this study was found to be 18.62% and 7.12%, respectively, which is lower than 35.7% and 9.7% reported by Nigam et al [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 Though, B blood grouped people affected more frequently, but our study haven't found any significant relationship between disease severity and ABO group and Rhesus grouping like other studies. 17,19,20,23,25 The current study had revealed that patients' age, occupation, history of smoking, high BMI and presence of underlying diseases were significantly associated with the severity of COVID-19. In our study we found 81.1% of the COVID-19 significantly managed at home level, 13.9% at general medical wards, 3.3% at HDU level and only 1.6% at ICU.…”
Section: Discussionmentioning
confidence: 64%
“…However, a large study conducted among blood donors in the central part of Bangladesh revealed 37.5%, 31.8%, 21.8% and 8.9% for B, O, A and AB respectively; and Rhesus positive and negative were 96.79% and 3.2% respectively. 25 Distribution of ABO group in the study population of Jashore, Bangladesh had been shown 39.6%, 29.1%, 22.5% and 11.5% for B, O, A and AB respectively; and Rhesus positive and negative were 95.5% and 4.5% respectively, whereas the other studies have reported that blood group A people were more susceptible to COVID infection. 17,18,19,20 However, the other study has reported highest and lowest vulnerable to get COVID-19 infection among blood group of B and AB people respectively which is very similar to our study.…”
Section: Discussionmentioning
confidence: 88%